Realization of Phrases in Ambon Malay - Thenu, Firdawati (Alphabet, 2026)
Despite the rich linguistic diversity of eastern Indonesia, the structural properties of phrase formation in Ambon Malay remain underexplored, particularly within formal syntactic frameworks such as Generative Transformational Grammar. This lack of systematic description creates a gap in understanding how phrase structures in regional Malay varieties are organized and how they contribute to broader typological and theoretical discussions in syntax. Addressing this gap, this study aims to analyze the realization of phrase structures in Ambon Malay using a Generative Transformational approach. The data consist of more than 200 linguistic instances collected through elicitation and recording techniques involving native speakers. The findings reveal several distinctive patterns of phrase structure in Ambon Malay. First, noun phrases are formed either by an optional quantifier preceding the noun or by a head noun followed by a possessive construction. This possessive element may optionally be extended by adjectives, adverbials, demonstratives, or prepositional phrases. Second, verb phrases are constructed through optional aspectual, modal, and intensifying markers, followed by serial verb constructions or adverbials, and auxiliaries preceding the main verb. Third, adjective phrases consist of a head adjective optionally modified by intensifiers or comparative markers. Fourth, adverbial phrases are structured around a head adverb of manner, optionally accompanied by intensifiers. Finally, prepositional phrases are formed by optional directional or locative markers followed by a preposition and a noun phrase. These findings demonstrate that Ambon Malay exhibits a unique and systematic ordering of phrase elements, which may differ from standard Malay varieties. The study highlights that such structural configurations can be classified as either grammatical or ungrammatical within the language system, thereby underscoring the need to formalize phrase structure rules specific to Ambon Malay. This research contributes not only to the descriptive documentation of eastern Indonesian languages but also to the development of syntactic theory by incorporating data from underrepresented linguistic contexts.